Nitrogen Input Effects on Herbage Accumulation and Presence of Pasture Plant Species. (1st July 2013) - Guretzky, John A.; Schacht, Walter; Snell, Laura; Soper, Jonathan; Moore, Stephanie; Watson, Andrea; Klopfenstein, Terry
Abstract : Long‐term responses of pasture plant species to management strategies that vary amount and form of N inputs form a knowledge gap. Our objective was to determine how supplementation of grazing beef cattle ( Bos taurus ) with corn ( Zea mays L.) dried distillers grains plus solubles (DDGS) in unfertilized pasture (SUPP) affects annual herbage accumulation and presence of plant species and functional groups relative to unsupplemented beef cattle on unfertilized (CONT) and N‐fertilized (FERT) smooth bromegrass ( Bromus inermis Leyss.) pasture. We addressed this objective in the sixth (2010) and seventh (2011) years of a long‐term experiment in eastern Nebraska, where N input from DDGS supplementation and urea fertilizer averaged 0, 43, and 90 kg ha –1 yr –1 within CONT, SUPP, and FERT, respectively. For these years, annual herbage accumulation averaged 6.87, 6.80, and 10.58 Mg ha –1 (LSD = 1.49) and 66.5, 66.2, and 76.0% of herbage accumulated by 25 June (LSD = 5.3) in CONT, SUPP, and FERT, respectively. Smooth bromegrass occurred in 99.8% of 0.1‐m 2 pasture quadrats regardless of treatment. Cessation of N fertilizer input, however, increased presence of annual foxtail ( Setaria spp.), annual graminoids, and annuals among quadrats in CONT relative to FERT. Supplementation of DDGS, while shown in previous studies to improve weight gains and N use efficiency in cattle, supplied enough N through excretion to provide an intermediate level of resistance to annual weeds. Nitrogen excreted from cattle supplemented with DDGS, however, did not affect herbage accumulation in subsequent years.